The cry of Tamar : violence against women and the Church's response - Cooper-White, Pamela, 1955- (Minneapolis, MN : Fortress Press, 2012)
In this comprehensive, practical, and gripping assessment of various forms of violence against women, Pamela Cooper-White challenges the Christian churches to examine their own responses to the cry of Tamar in our time. She describes specific forms of such violence and outlines appropriate pastoral responses. The second edition of this groundbreaking work is thoroughly updated and examines not only where the church has made progress since 1995 but also where women remain at unchanged or even greater risk of violence.
Power and violence against women -- Images of women: pornography and the connection to violence -- Sexual harassment and stalking -- Rape and sexual assault -- Battering -- Sexual abuse by clergy -- Sexual abuse of children -- The pastors as "wounded healer" -- Ministry with men who use violence -- Empowering women -- Reconciliation: moving beyond individual forgiveness to communal justice.
Includes bibliographical references (pages 264-329) and indexes.
Keywords: Women -- Crimes against -- Religious aspects -- Christianity; Violence -- Religious aspects -- Christianity; Church work with women; Women -- Pastoral counseling of